Applying action research to establish functional producer groups and value-adding producer organisations in southern Myanmar. Issue 1 (2nd January 2023) - Esnard, Randel; Lyne, Michael; Kartikasari, Ani; Old, Kevin
ABSTRACT: A project commissioned in 2017 to upgrade agribusiness value chains in southern Myanmar required functional producer groups to manage and sustain its transactional and value-adding interventions. This practical note describes the action research processes used to design, initiate, and develop these groups. It highlights key lessons and offers practitioners evidence-based guidelines to consider when collective action is required to link smallholders with preferred markets. Training and mentoring are important, but more effective if preceded by negotiation and acceptance of a constitution embedding good governance practices and investor-friendly institutional arrangements that groups can customise to support their business strategies.